Training educators of adults : the theory and practice of graduate adult education - Brookfield, Stephen (Routledge, 2019)
Originally published in 1988, this book provides perspective on conceptualisations of adult education in the late 20th century, the range of providing agencies and the varying orientations towards defining the role of the adult educator. It draws together and contextualises a selection of the most important readings on adult education theory and practice. The book will help develop critically reflective practitioners on adutl education courses - educators aware of the assumptions underlying their practice and capable of identifying theories and placing both theory and practice within the wider and ever-changing socio-politico context.- Resumé vydavatel
Originally published in 1988 by Routledge.
Keywords: vzdělávání dospělých -- Spojené státy americké; pedagogové -- Spojené státy americké; adult learning -- United States; educationalists -- United States; elektronické knihy; eseje; sborníky; electronic books; essays; papers of several authors